Clinical and cognitive correlates of visual hallucinations in dementia with Lewy bodies. Issue 5 (21st December 2012) - Cagnin, Annachiara; Gnoato, Francesca; Jelcic, Nela; Favaretto, Silvia; Zarantonello, Giulia; Ermani, Mario; Dam, Mauro
Abstract : Background: The presence of recurrent complex visual hallucinations (VHs) is a core feature of dementia with Lewy bodies (DLB). The aim of this study was to investigate which clinical and neuropsychological characteristics are associated with VHs and their predictive value over a 1 year follow-up. Methods: 81 DLB patients, 41 with (VH+) and 36 without (VH−) VHs, and 45 patients with Alzheimer's disease (AD), were enrolled. All participants underwent extensive neuropsychological testing. Visual–spatial and perceptual abilities were evaluated with the Visual and Object Space Perception (VOSP) battery. Fluctuations in attention, rapid eye movement sleep behaviour disorder (RBD) symptoms, extrapyramidal signs and behavioural disturbances were studied with dedicated clinical scales. Results: The presence of VHs was associated with older age and later disease onset, but not with disease duration or with fluctuations, RBD or parkinsonism severity. Cognitive correlates of VHs were deficits in visual attention (digit cancellation: p<0.005) and executive functions (clock drawing: p<0.05; digit span forward: p<0.05) on a background of a slightly worse global cognitive performance (Mini-Mental State Examination: p=0.05). Visual–perceptual and visual–spatial deficits were significantly worse in DLB than in AD patients (VOSP subtests scores 1, 6, 7 and 8) but were not different in DLB VH+ and VH−, except for subtest 6. Poor performance in the visual attention task was an independent predictor of VHs. Discussion: Impairment of visual–spatial and perceptual abilities in DLB represents a disease related cognitive signature, independent of the presence of VHs, for which it may represent a predisposing condition. Visual attention, instead, is the main cognitive determinant for the genesis of VHs.